O modelo de ensino confessional e o fortalecimento da concepção laica de Estado - Branco, Gustavo Leite Castello (2017)
The main goal of the current research was to study the so called “Confessional Model of Religious Teaching” and its relationship with the Brazilian Lay State. The purpose was to verify whether this Model is apt to contribute with a formation that is coherent with the constitutional principles of respect to diversity and to pluralism. Therefore this research is Exploratory regarding its objective and Qualitative regarding its approach. Researchers of Religious Sciences as a whole have recognized three “models” of Religious Teaching in the History of Brazil: the Confessional or Catechetical; the Theological or Inter-Confessional; and the Model of the Religious Sciences or Inter-Religious. The latter is also known as “NonConfessional Model”. The first chapter critically analyzed this classification and stated that it reflects a fragmentation typical to the contemporary Western worldview, that is, the dualism between knowledge/science/public space versus beliefs/religion/private space. According to this epistemological perspective, in the context of a lay State, the so called “Confessional Religious Teaching” would be an impracticable teaching in the Public Educational System while a tolerable teaching in the Private Educational System. In both cases such a teaching would fall short from promoting the constitutional ideals of pluralism and respect to cultural and religious diversity. The second chapter analyzed the coherence of this worldview from the epistemological perspective of the philosopher Michael Polanyi and the Theologian Lesslie Newbigin. This analyses was able to clarify that the division between what is “confessional” and what is “scientific” is not as absolute as it is usually assumed to be. It also demonstrated that faith, reason, and tradition necessarily operate together in the process of elaboration of all true human knowledge. While the former two chapters present a study with a bibliographical nature, the third chapter uses the method called Research as Survey in order to develop a field study. Therefore, building on the epistemological reflections made in the previous chapter, it adds a specific study about the relationship between Confessional Teaching and Brazilian laicity, deals with the practice of proselytism and its prohibition during the classes of Religious Teaching, and analyzes the experience of two confessional schools from the Private Educational System in the city of João Pessoa – PB: a Roman Catholic one and a Protestant one. Finally it is demonstrated that the contemporary Confessional Teaching should be distinguished from the Catechetical Model that was practiced in the past history of Brazil. The research concludes that Confessional Teaching is not only practicable in the context of the Brazilian laicity but is also able to promote and strengthen some fundamental values to Brazil and to the process of formation of its citizens.